Communicating About Routine Childhood Vaccines: Meta-Analysis of Parental Attitudes, Behaviors, & Vaccine Hesitancy - (:unkn) unknown (My University, 2020)
As scientific and medical communities research the next generation of vaccines, medical providers and parents observe the current routine vaccination schedules published for children today. And despite the fact protection is available from a number of preventable diseases through the use of safe, reliable, and accessible vaccines, Vaccine Hesitancy VH (delaying or refusing vaccination for reasons other than accessibility) is a growing issue. Using meta-analysis to examine existing research on communication about routine childhood vaccines, the study explores parental attitudes, behaviors, and demographics using the Protection Motivation Theory PMT. The study explores categories influencing VH such as: alternative medicine, safety, side effects, religion, and governmental/pharmaceutical conspiracies. Findings confirm parental attitudes, behaviors, and demographics influence VH and offer effect size information by study category. Implications of understanding effect size by category may include support for provider selection and prioritization of effective communication strategies for reducing VH.
Keywords: meta-analysis; parental attitudes; routine vaccines; vaccine hesitancy; VH